'We Cows are in a Very Serious Predicament': Constructions of Land Girls and Cattle in Britain in the Second World War. Issue 1 (5th May 2021) - Webb, Thomas; Summerfield, Penny; Riley, Mark; Pearson, Chris
Abstract: This article addresses understandings of a novel wartime labour force, the Women's Land Army, and of the cattle that a large proportion of its members worked with, in Britain during and after the Second World War. It draws on official records, publicity material, print media, memoirs and oral histories for an analysis of the gendered dynamics of the wartime management of the dairy herd, focusing on cultural constructions and their contradictions. We argue that Land Girls were widely depicted as urban interlopers even though many came from rural backgrounds, while cattle were sometimes seen as representatives of rural resistance and sometimes as vehicles for personal transformation.